Comparison of Cricothyroid Membrane Puncture Anesthesia and Topical Anesthesia for Awake Fiberoptic Intubation: A Double-Blinded Randomized Controlled Trial - Wang, Shaocheng; Hu, Chaoli; Zhang, Tingting; Zhao, Xuan; Li, Cheng (Frontiers in Medicine, 2021)
Background: Awake fiberoptic intubation (AFOI) is commonly used for patients with a difficult airway. The purpose of this study was to evaluate the efficacy of cricothyroid membrane puncture anesthesia and topical anesthesia during AFOI. Methods: A total of 70 patients (the American Society of Anesthesiologists score I-III) with anticipated difficult airways scheduled for nonemergency surgery with AFOI were randomly slated to receive cricothyroid membrane puncture anesthesia (n = 35) or topical anesthesia (n = 35). Each group received dexmedetomidine at a dose of 1.0 μg/kg and sufentanil at a dose of 0.2 μg/kg over 10 min for conscious sedation before intubation. The endoscopy intubation, post-intubation condition, and endoscopy tolerance as scored by the anesthetists were observed. The satisfaction of the operator regarding the procedure and the satisfaction of the patient 24 h after the surgery were also recorded. We recorded the success rate of the first intubation, intubation time, and hemodynamic changes during the procedure and also the adverse events. Results: Better intubation scores, operator satisfaction, and satisfaction of the patient were observed in the cricothyroid membrane puncture anesthesia group than in the topical anesthesia group (p < 0.05). The intubation time in the cricothyroid membrane puncture anesthesia group was less than that in the topical anesthesia group (p < 0.05). There were no significant differences in the patient tolerance scores, the success rate of the first intubation, hemodynamic changes, and adverse events between both the groups. Conclusion: Compared with topical anesthesia, cricothyroid membrane puncture anesthesia provided better intubation conditions and less intubation time with greater satisfaction of the patient and operator during endoscopic intubation. Clinical Trial Registration: URL: http://www.chictr.org.cn/showproj.aspx?proj=42636, Identifier: ChiCTR 1900025820.